Deporte de aventura como producto turístico en las siete cascadas del zapanal cantón la Maná, provincia de Cotopaxi - Peñafiel Aguilar, Jessica Lizbeth (2018)
The present investigation starts from the need to review the specific situation of the activities generated in a tourist attraction of the canton Pangua, border with the municipality of La Maná. To investigate the activities that are currently carried out regarding Adventure sports, verify the presence of local tour guides duly certified by the MINTUR and in turn a review of the weight that the tour operators have in the area. A P.M.R. in the improvement proposal in order to mitigate the high risk threat on the site. In this way, a calculation of the vulnerability index for visitors will be studied based on the previous events, which will allow mitigating the series of negative accidents that have occurred up to the present date. Once this action is determined, it will be sought to apply it as municipal ordinance and MINTUR for that the tourism operations generated have a guarantee of life and, above all, enjoyment.